ANALISIS BEBAN KERJA di BAGIAN PENGEPAKAN(Studi Kasus : PT Perkebunan Nusantara IX Kebun Batujamus Pabrik RSS Kerjoarum Karanganyar) - Sekar Pamungkas, Rachma, Ahmad Kholid Alghofari, ST.,MT (2017)
PT Perkebunan Nusantara IX Kebun Batujamus Kerjoarum is one of the goverment company engaged in the manufacture which produces rubber comodity in type of rubber smoke sheet with an average production of 6,500 kg per day. The production process is done mostly by using manpower. This research aims to indentify workload levels of workers both in mentally and physically, workers' complaint and give suggestions about number of operator. This research began by presenting NASA-TLX questionnaires and NBM to workers in packing division furthermore, CVL method used to determined workers' pulse when they work and gave suggestions about number of operators using manpower planning method. Based on the result of the research that has been done to the workers in packing division, obtained NASA-TLX score of 76 this score indicate that the workers' workload belongs to medium workload category. While based on NBM questionnaires body parts that experienced with pain are back, waist and right wrist. Pulse measurement by using CVL method to the workers in packing division had average result by 19%, these result indicate that the works does not cause any fatigue for the workers. The calculation result by using manpower planning concept is recommanding 7 workers instead of 6 workers.